Implementasi Proses Seleksi, Penempatan dan Gaji Terhadap Kinerja Karyawan di PT. Bank Syariah Indonesia KCP Medan Petisah - Munandar, Arief; Batubara, Maryam; Hasibuan, Reni Ria Armayani (Universitas Labuhanbatu, 2024)
This research aims to determine the implementation of the selection, placement and salary process on employee performance. Data collection methods using qualitative research and primary data obtained from interviews. The research results show that the selection process at Bank Syariah Indonesia KCP Medan Petisah uses 2 (two) methods: non-scientific methods and scientific methods. Implementation of the Selection, Placement and salary process on employee performance at PT. Bank Syariah Indonesia KCP Medan Petisah as follows. The workforce selection method applied by Bank Syariah Indonesia KCP Medan Petisah must follow the existing recruitment procedures at the Bank and determine the minimum qualifications in the form of a preliminary interview, selection process, educational background according to the position, and work experience of the job applicant. Implementation of the placement process includes determining human resource needs, recruitment, preparing a list of qualified employees. Conduct employee selection. The application of salaries includes the meaning of fairness in the Islamic concept, fair means clear and transparent, and fair means proportional.